Seasonal variation in occurrence of ischemic colitis: a retrospective study. (February 2017) - Yamanouchi, Satoshi; Ogawa, Sayaka; Kusunoki, Ryusaku; Miyaoka, Youichi; Fujishiro, Hirofumi; Kohge, Naruaki; Kinoshita, Yoshikazu
Objectives: We aimed to identify the clinical characteristics of ischemic colitis (IC) and to investigate the occurrence of seasonal variation. Methods: From January 2008 to December 2014, 368 had IC as the reason for their admission. A total of 364 patients were enrolled in this study. We investigated patient characteristics and seasonal variations in incidence. Results: The mean age (±standard deviation) of patients with IC at diagnosis was 66.8 (±16.9) years. Most patients had abdominal pain (341 cases), hematochezia (337 cases), and diarrhea (199 cases) as their chief complaints. The clinical courses of the disease were classified as transient (294 cases), stricture (17 cases), gangrenous (2 cases), and indeterminate types (51 cases). Although IC tended to occur less frequently in winter, the seasonal difference was not significant. Conclusion: There is currently no evidence for seasonal variation in hospital admissions for IC.